Pengaruh Struktur Kepemilikan Keluarga Terhadap Kinerja Perusahaan Pada Sektor Industri Barang Konsumsi - Evelyn Sutejo; Juniarti Juniarti Juniarti (Business Accounting Review, 2017)
Most companies in Indonesia have family ownership structures, which have advantages and disadvantages that affect the company performance. Empirical results from previous studies on the influence of family ownership structure on corporate performance when still had many inconsistencies. This study aimed to know the affect of family ownership structure on company performance measured by using performance measurement based on accounting that was Return on Assets (ROA). The control variables in this research were firm age and good corporate governance. The sample used in this research was 30 companies in the consumer goods industry sector in 2010 to 2015. The research method used was multiple regression analysis model.The result of this research proved that family ownership structure had negative affect but not significant to ROA. Variable of good corporate governance had significant negative affect to ROA. While the variable of firm age had significant positive affect to ROA.